1812. Impact of Rapid Identification of Blood Cultures With Antimicrobial Stewardship at Three Community Hospitals Within a Health System. (26th November 2018) - Su, Christy; Babic, Jessica; Schilling, Amy; Wanger, Audrey
Abstract: Background: The use of rapid diagnostic tests (RDT) in microbiology decreases time to pathogen identification (ID). When coupled with an Antimicrobial Stewardship Program (ASP), time to optimal antibiotics can be significantly reduced. The purpose of this study was to evaluate the impact of Verigene® Gram-Positive Blood Culture Test (BC-GP) and Gram-Negative Blood Culture Test (BC-GN) implementation with an ASP at three community hospitals within a health system with centralized microbiology services. Methods: A retrospective analysis was conducted to compare time to targeted antibiotics for treatment of bloodstream infections (BSI) before and after implementation of Verigene®. Patients were included with a positive blood culture for organisms detectable by Verigene BC-GP and BC-GN during September 2016 (pre-implementation group) and September 2017 (post-implementation group). Patients were excluded if positive blood culture had more than one organism, patient was actively being treated for an infection unrelated to blood culture or blood culture results were available after patient expired, was discharged or transferred. Targeted antibiotic therapy was defined as antibiotic therapy tailored toward pathogen based on ID and sensitivities. Each ASP pharmacist received Verigene® notifications in real-time. Secondary endpoints were in-hospital mortality, hospital length of stay (LOS), and days of vancomycin therapy. Results: A total of 93 patients were included in the final analysis with 42 patients in pre- group and 51 in post-group. Patients achieving targeted therapy during their hospital stay was 38 of 42 (90%) in the pre-group and 47 of 51 (92%) in the post-group. Of those who achieved targeted therapy, time to targeted therapy was 78.4 hours vs. 43.1 hours in pre-group vs. post-group, respectively ( P < 0.001). No significant difference was detected for in-hospital mortality or hospital LOS. Length of vancomycin therapy was decreased from 85.8 hours to 48.6 hours in post-group ( P < 0.001). Conclusion: Implementation of RDT in three community hospitals with a centralized microbiology laboratory resulted in a significantly improved time to targeted antibiotics in patients with BSI when combined with ASP pharmacist real-time notification. Disclosures: All authors: No reported disclosures.